Screening for HIV among presumptive and microbiologically confirmed tuberculosis patients in a tertiary care hospital, Puducherry - Pradeep, Kumar; Velavan, Anandan; Niranjan, Rajasekar; Samundeswari, Gopinathan; Purty, Anil J. (International Journal Of Community Medicine And Public Health, 2022)
Background: Screening of presumptive cases of TB for HIV is a challenge as it requires pre-test counselling and informed consent of the patients. This study aims to measure the proportion of presumptive TB cases who were screened for HIV status and their outcome. Methods: The present study was a record based cross sectional study comprising of all presumptive and confirmed cases of tuberculosis patients who visited PIMS during the study period, from June 2019 to June 2021. Percentage and proportions were used to express the outcome variable. Results: A total of 862(39.3%) out of 2,193 presumptive tuberculosis patients were screened for HIV in the last 2 years, out of which 9 patients (1%) turned positive. Out of 328 microbiologically confirmed tuberculosis patients we have screened 325(99%) patients and 6 (1.8%) patients were found to be positive. Conclusions: As per provide initiated HIV testing and counselling guidelines, screening of presumptive cases of TB yielded positive results in identifying additional cases of HIV positive patients.